New results in single linear quadratic optimal control - Ferrante, A.; Ntogramatzidis, Lorenzo (COC Publications, 2012)
This paper focuses on the singular infinite-horizon linear quadratic (LQ) optimal control problem for continuous-time systems. In particular, we are interested in the stabilising impulse-free solutions to this problem that can be expressed as a static state feedback. In particular we establish a link between the geometric properties of the so-called Hamiltonian system associated with the optimal control problem at hand and the so-called proper deflating subspaces of the Hamiltonian matrix pencil.